Flood vulnerability and resilience: Exploring the factors that influence flooding in Sarawak - Abid, S. K.; Sulaiman, N.; Wei, C. S.; Nazir, U. (2021)
Flooding is the most common natural disaster in Malaysia, resulting in chaos and disruptions to social and economic activities, damage to roads and railway tracks, vehicles, affecting the level of properties, loss of life, and rise in vulnerability. In addition to natural causes, floods are mainly attributed to continuous heavy rainfall, rapid development, unplanned urbanization, poor drainage system, and environmental degradation. This annual occurrence of floods has given a big impact on the lives of humans and other living beings. Due to the negative impact of floods, we need to pay serious attention and take alternative ways to reduce this disaster. This study aimed to investigate the vulnerability factors and understand the concept of vulnerability and resilience to manage floods in Sarawak. The researcher primarily focused on reviewing the printed and documented material of disasters in order to find the vulnerability factors. Based on the findings, it can be concluded that nature, human, and governance factors, contributed mostly to floods. The present study shows that vulnerability reduction along with emergency preparedness can reduce flood damages and fatalities. The innovative technologies must have to be considered to reduce vulnerability and build resilience for sustainable disaster risk reduction.